Effects and fate of TiO2 nanoparticles in the anaerobic treatment of wastewater and waste sludge. (15th September 2018) - Cervantes-Avilés, Pabel; Ida, Junichi; Toda, Tatsuki; Cuevas-Rodríguez, Germán
Abstract: The increasing use of TiO2 nanoparticles (NPs) in customer products has also increased the concerns about their effects in the environment. Anaerobic digestion is a process probably exposed to high concentrations of TiO2 NPs due to its application for wastewater and waste sludge treatment. In this work, it was studied the anaerobic digestion performance and the extracellular polymeric substances (EPS) production in presence of TiO2 NPs, as well as the fate of TiO2 NPs in anaerobic reactors. Results showed that methane production enhanced an average of 14.9% in presence TiO2 NPs, which is considered a positive effect. A strong affinity between TiO2 NPs and EPS was found, especially for proteins (PRO) and polysaccharides (PS) in the loosely and tightly bound EPS layers of microorganisms (LB-EPS and TB-EPS). Ti quantification indicated that 92% of the TiO2 NPs are removed by anaerobic sludge, while 8% remain in the treated effluent. Graphical abstract: Image 1 Highlights: Treated effluent quality is not affected by TiO2 NPs in anaerobic process. Methane production yield was enhanced by presence of TiO2 NPs. TiO2 NPs were adsorbed by polysaccharides and proteins contained in the LB-EPS. The main fate of TiO2 NPs after anaerobic digestion is still the sludge disposal. Presence of Ti in inoculum may confirm the arrival of TiO2 NPs to full scale plants.